Bottom Passing of Students at SMA Negeri 1 Binamu - Sufitriyono Sufitriyono; Irvan Irvan; Muhammad Akbar Syafruddin; Agus Sutriawan; Andi Sahrul Jahrir (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objective. This quantitative descriptive study aims to determine the volleyball bottom passing ability of Binamu State High School students. The data collection techniques used are tests and measurements. Materials and Methods. The population in this study were students at SMA Negeri 1 Binamu, with a sample size of 22 students. The instrument used in this research was a test, namely the Brumbach forearm pass wall-volley test. The data analysis technique used is a descriptive percentage. Results. The research data shows that the maximum score that students can achieve is 39, and the minimum score is 24. The research data that has been classified shows that the ability to pass under volleyball in PJOK Learning at SMA Negeri 1 Binamu is in the